The Influence of Influencer Marketing, Online Customer Reviews, and Brand Image on Consumer Purchasing Decisions on Avoskin Products - Cahyaningrum, Tri Mukti; Prabowo, Heri; Ervina Indiworo, Rr Hawik (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of Influencer Marketing, Online Customer Reviews, and Brand Image on Consumer Purchasing Decisions on Avoskin Products (Case Study of PGRI Semarang University Students)’’. The population used in the research were active undergraduate students from the 2020-2023 class at PGRI University Semarang, totaling 6,807 students and the sample used was 377 students who used Avoskin skincare products using purposive sampling. Data analysis in the study used Smart PLS version 4.0 software. The results of this research show that the Purchase Decision is (0.610), this proves that the strength of the influencer marketing, online customer review and brand image variables can be explained through the Purchase Decision variable of 61% (moderate category).